Dogs from public city parks as a potential source of pollution of the environment and risk factor for human health - MARKO, RISTICÂ´; SANDA, DIMITRIJEVICÂ´; ALEKSANDAR, VIÅ NJICÂ´; DANICA, BOGUNOVICÂ´; BOJAN, GAJICÂ´ C; MIODRAG, STOJANOVICÂ´; TAMARA, ILICÂ´ (The Indian Journal of Animal Sciences, 2020)
A study was undertaken to determine the prevalence of zoonotic parasites in faeces of dogs who were visiting the public parks and to evaluate the risk they represented for the people and children visiting the same places. Parasitological analysis was performed on 300 samples of faeces, collected from public parks of the city of Niš (Tvrd– dava Park, C´ air Park, Sveti Sava Park); from autumn 2018 and spring 2019. Using standard qualitative and quantitative methods of coprological diagnostics, the presence of protozoa (Cystoisospora spp.), nematodes (Toxocara canis, Toxascaris leonina, Ancylostoma caninum / Uncinaria stenocephala, Trichuris vulpis and Capillaria aerophila), cestodes (Dipyllidium caninum, Taenia spp.) and trematode Alaria alata was determined. The prevalence of endoparasitoses were 58–70%, and the most prevalent were those of medium intensity. Depending on the research period, the four most frequent endoparasites were T. canis (36.66–38%), ancylostomatidae (24.66–32%), T. vulpis (20–28%) and A. alata (28%).